Humor translation from Spanish into English -of the movie "Asumare" - Guaylupo Polo, José Antonio Emanuel (2018)
The main objective of this research was to determine the elements that hinder the translatability of the humor of the Spanish to English in the scenario of the film "Asu Mare" Trujillo 2015. El type of study is focused on the under- standing, design, was the study of cases. Was used as an instrument of collection of information the registration form; two basic techniques of analysis was used for the analysis of information collected from field: analysis of contents to transcribe scenes from the film 'Asu Mare' and domain analysis to translate all the information collected. From this study, it can be concluded that: there are at least seven difficulties to for the translatability of humor, these are semantic, syntactic, morphological, lexical ordering, pragmatic, phonetic and physiotherapy. Not all the elements that make it difficult for the translatability of humor are translatable; on some occasions, it is necessary to resort to the adaptation of a term from one language to another so as to not lose the original sense of humor. This, in turn, has manifested itself most often in elements that hinder the translatability of humour or phonetic level and physiotherapy, which should be noted, they were not included in the present study, but they played a fundamental role at the time of analyzing the translatability of humor.